Monetary Policy and the Stock Market: Time-Series Evidence - Andreas Neuhierl; Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2016)
We construct a slope factor from changes in federal funds futures of different horizons. Slope predicts stock returns at the weekly frequency: faster monetary policy easing positively predicts excess returns. Investors can achieve increases in weekly Sharpe ratios of 20% conditioning on the slope factor. The tone of speeches by the FOMC chair correlates with the slope factor. Slope predicts changes in future interest rates and forecast revisions of professional forecasters. Our findings show that the path of future interest rates matters for asset prices, and monetary policy affects asset prices throughout the year and not only at FOMC meetings.
Keywords: E31; E43; E44; E52; E58; G12; 330; return predictability; policy speeches; expected returns; macro news